1985
DOI: 10.1016/0014-5793(85)81111-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the glucocorticoid hormone receptor with ribonucleic acid

Abstract: The hypothesis that the glucocorticoid hormone receptor interacts with RNA has been tested in cultured rat hepatoma cells. The receptor was covalentIy labeled with radioactive dexamethasone mesylate, and putative RNA-receptor complexes were stabilized by either cell-free crosslinking using formaldehyde or irradiation of intact cells. After chemical cross-linking in vitro, the receptor displayed the buoyant density of a ribonucleoprotein in CsCl gradients. After photochemical crosslinking in cells labeled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…receptors that interact with additional, less well characterized proteins (12,37,60) or with RNA (3,17,61).…”
mentioning
confidence: 99%
“…receptors that interact with additional, less well characterized proteins (12,37,60) or with RNA (3,17,61).…”
mentioning
confidence: 99%
“…The gel was dried and exposed to an XAR-5 Kodak film using Dupont intensifying screens. To prepare RNA markers, total RNA was extracted from rat hepatoma cells, incubated with [3H]uridine [21] and co-electrophoresed. The small RNAs were identified by comparison with published data [45].…”
Section: Labeling and Identification Of R N Amentioning
confidence: 99%
“…Housley and Pratt [31] demonstrated that RNase removed a 21 000-M, component associated with the purified receptor from mouse L-cells. In addition, it was reported that the transformed receptor from mouse At-T20 cells could bind endogenous tRNA, to give intermediate transformed receptor species of greater size [19, 321. An artefactual association of RNA with the receptor during the preparation of cytosol was unlikely since we had previously demonstrated that the untransformed receptor of rat hepatoma cells behaves as a ribonucleoprotein after crosslinking not only in vitro but also in intact cells [21]. Experiments performed to discriminate between a nonspecific RNA-receptor association in cytosol and the possibility that RNA is an integral component of the untransformed highly purified receptor, have yielded contradictory results [20, 331. On the one hand, it was shown that the 9-S untransformed receptor was RNase-insensitive [33].…”
mentioning
confidence: 99%
“…The nuclear skeleton appears to support DNA replication (Pardoll et al, 1980 ;Tubo et al, 1985) and transcription (Robinson et al, 1983 ;Ciejek et al, 1983 ; by tightly anchoring DNP. This structure also binds hnRNP (Herman et al, 1978 ;Miller et al, 1978a ;Van Eekelen and Van Venrooij, 1981) and snRNP (Miller et a/., 1978b ;Gallinaro et al, 1983) Rousseau, 1985). RNA is a potent competitor for the binding of receptor-androgen (Liao et al, 1980), -oestrogen (Feldman et al, 1981 ;Chong and Lippman, 1982), and -dexamethasone (Tymoczko et al, 1982) (Palmiter and Carey, 1974 ;Cox, 1977) ; similarly, oestrogen or progesterone was demonstrated to affect the half-life of coinalbumin mRNA in chick oviduct (Mc Knight and Palmiter, 1979), and androgen to modulate the half-life of prostatic binding protein mRNAs (Page and Parker, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, receptor-RNA interaction might not only be an important mediator of RNA processing and transport, but also a component of receptor processing and/or transport back to the « cytosol ». Recycling of nuclear steroid-receptors to their cytosolic form nevertheless remains an enigma (Horwitz and Mc Guire, 1980 ;Kasid et al, 1984), yet there is evidence that untransformed « cytosolic receptors » can exist complexed with RNA (Chong and Lippman, 1982 ;Tymoczko and Phillips, 1983 ;Economidis and Rousseau, 1985 …”
Section: Introductionmentioning
confidence: 99%